Human Cell - Kataoka, Hiroaki; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Human Cell is the official English-language journal of the Japan Human Cell Society. The journal serves as a forum for international research on all aspects of the human cell, encompassing not only cell biology but also pathology, cytology, and oncology, including clinical oncology. Embryonic stem cells derived from animals, regenerative medicine using animal cells, and experimental animal models with implications for human diseases are covered as well. Submissions in any of the following categories will be considered: Research Articles, Cell Lines, Rapid Communications, Reviews, and Letters to the Editor. A brief clinical case report focusing on cellular responses to pathological insults in human studies may also be submitted as a Letter to the Editor in a concise and short format. Not only basic scientists but also gynecologists, oncologists, and other clinical scientists are welcome to submit work expressing new ideas or research using human cells.
Keywords: Gynecology; Oncology; Reproductive medicine; Surgery; Cell biology; Stem cells; Cell Biology; Oncology; Surgery; Gynecology; Reproductive Medicine; Stem Cells